Treatment with either COX‐2 inhibitor or 5‐LOX inhibitor causes no compensation between COX‐2 pathway and 5‐LOX pathway in chronic aluminum overload‐induced liver injury in rats. (2nd April 2019) - Xia, Hui; He, Qin; Wang, Hong; Wang, Yongming; Yang, Yang; Li, Yuke; Zhang, Jiahua; Chen, Zhihao; Yang, Junqing
Abstract: This study was designed to observe the compensation between cyclooxygenase‐2 pathway and 5‐lipoxygenase pathway in chronic aluminum overload‐induced liver injury rats. A rat hepatic injury model of chronic aluminum injury was established by the intragastric administration of aluminum gluconate (Al3 + 200 mg/kg per day, 5 days a week for 20 weeks). The COX‐2 inhibitor [meloxicam (1 mg/kg)] and 5‐LOX inhibitor [caffeic acid (30 mg/kg)] were intragastrically administered 1 h after aluminum administration. The histopathology was detected by hematoxylin‐eosin staining. A series of biochemical indicators were measured with biochemistry assay or ELISAs. The expressions of COX‐2 and 5‐LOX were measured by immunohistochemistry. Our experimental results showed that aluminum overload caused a significant damage to the liver and also significantly increased the expressions of COX‐2, 5‐LOX and the levels of inflammation and oxidative stress. The administration of meloxicam and caffeic acid significantly protected livers against histopathological injury, significantly decreased plasma ALT, AST, and ALP levels, significantly decreased TNF‐α, IL‐6, IL‐1β levels, and oxidative stress. However, the administration of caffeic acid did not significantly increase the expression of COX‐2 compared with the model group. On the other hand, the administration of meloxicam also did not significantly increase the expression of 5‐LOX compared with the model group. Our results indicate that there is no compensation between COX‐2 pathway and 5‐LOX pathway by inhibiting either COX‐2 or 5‐LOX in chronic aluminum overload‐induced liver injury rat.